American labor's role in less developed countries. A report on a conference held at Cornell University, October 12-17, 1958. [With a forew. by M.P. Catherwood (New York State School of industrial and labor relations])
Publications of the New York State school of industrial and labor relations, a unit of the State University of New York, at Cornell University, N.Y.